The extensive amplification of heterochromatin in Melipona bees revealed by high throughput genomic and chromosomal analysis - Pereira, Jaqueline A.; Milani, Diogo [UNESP]; Ferretti, Ana Beatriz S. M. [UNESP]; Bardella, Vanessa B. [UNESP]; Cabral-de-Mello, Diogo C. [UNESP]; Lopes, Denilce M. (Springer Nature, 2021)
Satellite DNAs (satDNAs) and transposable elements (TEs) are among the main components of constitutive heterochromatin (c-heterochromatin) and are related to their functionality, dynamics, and evolution. A peculiar case regarding the quantity and distribution of c-heterochromatin is observed in the genus of bees, Melipona, with species having a low amount of heterochromatin and species with high amount occupying almost all chromosomes. By combining low-pass genome sequencing and chromosomal analysis, we characterized the satDNAs and TEs of Melipona quadrifasciata (low c-heterochromatin) and Melipona scutellaris (high low c-heterochromatin) to understand c-heterochromatin composition and evolution. We identified 15 satDNA families and 20 TEs for both species. Significant variations in the repeat landscapes were observed between the species. In M. quadrifasciata, the repetitive fraction corresponded to only 3.78% of the genome library studied, whereas in M. scutellaris, it represented 54.95%. Massive quantitative and qualitative changes contributed to the differential amplification of c-heterochromatin, mainly due to the amplification of exclusive repetitions in M. scutellaris, as the satDNA MscuSat01-195 and the TE LTR/Gypsy_1 that represent 38.20 and 14.4% of its genome, respectively. The amplification of these two repeats is evident at the chromosomal level, with observation of their occurrence on most c-heterochromatin. Moreover, we detected repeats shared between species, revealing that they experienced mainly quantitative variations and varied in the organization on chromosomes and evolutionary patterns. Together, our data allow the discussion of patterns of evolution of repetitive DNAs and c-heterochromatin that occurred in a short period of time, after separation of the Michmelia and Melipona subgenera.
Keywords: Fluorescence in situ hybridization; Repeatome; Satellite DNAs; Stingless bees; Transposable elements